Effect of Cooperative Type Model Stad and Student Learning Motivation on Learning Outcomes of Integrated Thematic Learning in Class IV Elementary School - Resca Corrina Sarie; Farida Mayar (International Journal of Educational Dynamics, 2019)
This research originated from the problem of low student learning outcomes in the elementary school of Padang. This is due, among other things, to learning that is still dominated by teachers. Students are still focused on the ways taught by the teacher and have not been able to cooperate in groups well. To overcome this problem, the STAD type cooperative learning model is used. This study aims to determine the effect of the STAD type cooperative model and student learning motivation on integrated thematic learning outcomes. The type of research used is quasi experiment. The study population was all fourth grade students of SDN 20 Indarung Padang who were enrolled in semester 2 of the 2018/2019 school year with a total of 43 students. The sample selection was done by random sampling. The experimental class is class IVA students of SDN 20 Indarung Padang and as a control class is grade IVB of SDN 20 Indarung Padang. The research instruments were learning motivation questionnaires and written tests. Data analysis was performed using the t test and two-way ANAVA for interaction. The results of the analysis show that: (1) Student learning outcomes in Theme 8 using the STAD type cooperative model are better than conventional methods. (2) Student learning outcomes in Theme 8 which have High Learning Motivation using the STAD type cooperative model are better than conventional methods. (3) Student learning outcomes in Theme 8 which have low learning motivation using the STAD type cooperative model are better than conventional methods. (4) There is an interaction between the cooperative type STAD model and conventional methods and learning motivation towards student learning outcomes. Keywords: STAD Type Cooperative Model, Learning Motivation, Learning Outcomes, Integrated Thematic Learning